Adoption and usage of ICTs in Jordanian higher education institutions - Khasawneh, Mohammad M.F.; Ibrahim, Huda (2013)
Information and Communication Technology (ICT) is considered in a beginning stage in the developing countries such as Arab world especially in the field of teaching and learning process.Jordan as one of the developing countries though appreciates the importance of Higher Education Institutions (HEIs) and their role in achieving an economic prosperity through the development of human resources; unfortunately, the adoption of ICT is quite low among the academic staff in the public HEIs.This study therefore, is concerned with the improvement of teaching and learning process through the adoption of ICT among the academic staffs in the Jordanian higher education institutions.The main purpose of this study is to examine the potential prominent factors related to the adoption and usage of ICT in the public Jordanian HEIs among the teaching staff. The main challenge of the study is to provide such an understanding on the ICT usage by applying the Diffusion of Innovation (DOI) theory. The findings show that attitude towards technology (ATT), have positively affected the behavioural intention (BI) to use ICT in the higher educational system among academic staff.There is also a significant relationship between academic staff’s perception of technology characteristics and their attitude towards using the technology in the educational system.